Industry 4.0 and Industry 5.0—Inception, conception and perception. (October 2021) - Xu, Xun; Lu, Yuqian; Vogel-Heuser, Birgit; Wang, Lihui
Highlights: A concise account of Industry 4.0 and Industry 5.0 is given. Questions are raised about the situation of Industry 4.0 and Industry 5.0 co-existing. Discussions, guided by the questions, are given to clarify the two terminologies. Abstract: Industry 4.0, an initiative from Germany, has become a globally adopted term in the past decade. Many countries have introduced similar strategic initiatives, and a considerable research effort has been spent on developing and implementing some of the Industry 4.0 technologies. At the ten-year mark of the introduction of Industry 4.0, the European Commission announced Industry 5.0. Industry 4.0 is considered to be technology-driven, whereas Industry 5.0 is value-driven. The co-existence of two Industrial Revolutions invites questions and hence demands discussions and clarifications. We have elected to use five of these questions to structure our arguments and tried to be unbiased for the selection of the sources of information and for the discussions around the key issues. It is our intention that this article will spark and encourage continued debate and discussion around these topics.